Exchange Rate Pass-Through and Inflation: Policy Insights for Vietnam Based on Comparative Analyses Across Asia - Anh T. Q. Dang,; Anh D. Pham, (Asian Academy of Management Journal, 2024)
The exchange rate is a crucial macro indicator for any open economy, whereby any change in the rate would influence, to a certain extent, various socioeconomic facets. One of the significant impacts is revealed in the pass-through of exchange rate variations to price inflation, also known as the exchange rate pass-through (ERPT). This paper explores the effect of ERPT on domestic inflation in Vietnam by comparing with other Asian economies. Specifically, pass-through mechanisms are examined for every single price as well as a distribution chain from import price index (IMP), producer price index (PPI) to consumer price index (CPI). The empirical results show that exchange rate shocks positively influence the price changes in Vietnam as well as in other Asian countries. According to Cholesky decomposition, the exchange rate plays a limited role in regulating CPI movements. Besides, world commodity prices are found to have a significant impact on domestic inflation across the sample-countries. Our findings reveal profound implications for monetary policy management and price stability.